Brazing behavior of ultrafine cemented carbide with stainless steel - Yang, Tian-en; Yang, Li; Xiong, Ji; Sun, Lan; Guo, Zhi-xing; Zheng, Xiao-ming (Journal of Central South University, 2014)
In order to investigate the effects of brazing temperature, heating rate and cooling methods on shear strength, hardness, magnetic saturation and coercivity of the ultrafine cemented carbide, the ultrafine cemented carbide was fabricated according to conventional powder metallurgical procedures, and then brazed to the stainless steel with silver-based filler alloy by supersonic frequency induction brazing. The microstructure was observed using scanning electron microscope (SEM), energy dispersive spectroscopy (EDS) and the magnetic properties were tested utilizing coercimeter and cobalt magnetism instrument. The results show that no micro-crack is found in the cemented carbide after brazing because of silver-based sandwich compound used as filler alloy. In the melted silver layer, there is more carbon in the region adjacent to the cemented carbide. Varied shear strengths, hardnesses, magnetic saturations and coercivities are present under different brazing temperatures, heating rates and coolings. This phenomenon is correlated with some factors such as wettability and fluidity of filler alloy, brazing stress, oxidation of cemented carbide, and allotrope transition of cobalt. Shear strength reaches the maximum of 340 MPa and hardness of ultrafine cemented carbide remains 1879 HV at the brazing temperature of 730 °C. The carbon content decreases with the increase of brazing temperature, and it increases with the of increase of the heating rate. What’s more, the lowest magnetic saturation reaches 81.8% of the theoretic value, and there is no η phase found under this condition.